ESG risk profiles and financial performance: A multi-sector analysis of market returns - Sudarmaji, Eka; Yatim, M Rubiul; Herlan; Al-Ansori, Arya Jati Kusuma (International Journal of Business, Economics and Management, 2025)
This study aims to clarify how Environmental, Social, and Governance (ESG) risk components environmental, social, governance, and controversy scores, influence year-to-date (YTD) returns while considering industry-specific effects. It explores the relationship between ESG risk profiles and financial performance across 377 S&P 500 companies from various sectors. A multi-method analytical framework was employed on a cross-sectional dataset (January–December 2023) obtained from Kaggle, which includes Yahoo Finance financial data and Sustainalytics ESG measures. Regression models based, extended, and complete with industry controls quantified the ESG-return link. Descriptive statistics, ANOVA, and clustering approaches identified sectoral ESG risk patterns. When paired with sector controls, ESG risk ratings accounted for 41.2% of YTD return variation, indicating non-linear effects: moderate-risk companies usually outperformed high- and low-risk counterparts. Sector heterogeneity was notable; Energy and Utilities (high ESG risk) showed different return patterns than Technology and Real Estate (low ESG risk). While controversy ratings had little predictive value, environmental and governance concerns were the main drivers of ESG scores. Industry was underscored as a significant risk predictor; a logistic regression classified sectors by ESG risk with 98.9% accuracy. Since ESG’s financial influence is sector-dependent, investors should consider industry context and ESG profiles in their decisions. Some industries, such as technology, may emphasize governance, while companies in high-risk industries, like Energy, may prioritize environmental concerns. These findings assist managers and legislators in customizing ESG plans to fit relevant sector-specific elements.